2020
DOI: 10.7150/thno.37423
|View full text |Cite
|
Sign up to set email alerts
|

WNT signaling inducing activity in ascites predicts poor outcome in ovarian cancer

Abstract: High grade serous carcinoma of the ovary, fallopian tube, and peritoneum (HGSC) is the deadliest gynecological disease which results in a five-year survival rate of 30% or less. HGSC is characterized by the early and rapid development of metastases accompanied by a high frequency of ascites i.e. the pathological accumulation of fluid in peritoneum. Ascites constitute a complex tumor microenvironment and contribute to disease progression by largely unknown mechanisms.Methods: Malignant ascites obtained from HGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Peritoneal metastasis of HGSOC is also promoted by WNT5A, which is abundant in ascites [60,62]. As previously mentioned, WNT5A activity (non-canonical PCP signaling) promotes the metastatic stem-cell like behavior of HGSOC cells and confers a poor prognosis.…”
Section: Metastasismentioning
confidence: 85%
See 2 more Smart Citations
“…Peritoneal metastasis of HGSOC is also promoted by WNT5A, which is abundant in ascites [60,62]. As previously mentioned, WNT5A activity (non-canonical PCP signaling) promotes the metastatic stem-cell like behavior of HGSOC cells and confers a poor prognosis.…”
Section: Metastasismentioning
confidence: 85%
“…The regulation of canonical and non-canonical Wnt signaling is complex and dysregulation resulting in hyperactivation or loss of different components of the signaling pathways can ultimately lead to tumorigenesis or disease progression. For example, activation of non-canonical Wnt signaling by overexpression of WNT5A (non-canonical PCP Wnt protein) in ascites fluid promotes metastatic stem-cell like behavior in HGSOC cells and results in worse survival [60]. Our group demonstrated that WNT5A was significantly underexpressed in primary human EOC compared to normal ovarian surface and fallopian tube (FT) epithelial tissue and that loss of WNT5A correlates with worse survival [42].…”
Section: Tumorigenesismentioning
confidence: 94%
See 1 more Smart Citation
“…The Wnt/β-catenin pathway controls various cellular processes of cancer biology, such as cell proliferation, differentiation, and maintenance of pluripotency (17). The function of the Wnt/β-catenin pathway on EC growth had been well-established (18). β-Catenin maintains epithelial cell integrity, an important barrier for blocking tumor metastasis (19).…”
Section: Introductionmentioning
confidence: 99%
“…l The apoptosis of indicated cells was examined by caspase-3 activity analysis. **P < 0.01 Polarity (PCP) pathway has also been studied in recent years due to its role in controlling cancer cell functions [51][52][53]. Current study determined the activation of OIP5-AS1/miR-300/YY1 feedback loop on canonical WNT pathway.…”
Section: Discussionmentioning
confidence: 96%